Pengembangan Buku Ajar Pendidikan Kerajinan Tangan Untuk Meningkatan Pengetahuan Dan Kemampuan Mahasiswa S-1 GSD FIP Unesa - Suprayitno, (Pendidikan Sekolah Dasar, 2010)
The learning process is a complicated process because it doesnt simply absorb information, but involves a variety of activities and actions to take, especially if the desired outcome of good learning (Abin Syamsudin, 1998). This research is the development of the survey approach, demonstration, questionnaires, and performance test with the aim of an effort to improve knowledge and skills students handicraft education S-1 PGSD Unesa FIP. The results of the test craft ability in percentage increased significantly by 4.70%. As for the performance test results of  in general there are significant differences, prior to and after guidance. From the analysis it can be concluded that, (1) with the training activities can motivate students to improve their knowledge and ability in the education of crafts, (2) to increase students knowledge and skills required the textbook that is easily understood and practical for students in studying at university, (3) a prototype of research results can be used as a handbook for students PGSD Unesa FIP.